Emotional intelligence and its relationship to the performance level of early childhood teachers in Hafr Al-Batin region, Saudi Arabia - Al-Shammari, Nada Remthan AlMukhtari (Journal of Educational and Psychological Sciences, 2023)
The study aimed to determine the extent to which emotional intelligence is available among early childhood female teachers in the Hafr Al-Batin region in the Kingdom of Saudi Arabia,. The descriptive analytical approach was used based on a questionnaire as a tool for addressing the analytical aspects of the topic of the study and to collect the primary data, which were distributed to the study population consisting of all early childhood teachers in the Hafr Al-Batin region in the Kingdom of Saudi Arabia during the first semester of the academic year (1442/1443 AH). The population consisted of (280) female teachers, from which a sample of (169) female teachers was selected. The data was analyzed using the SPSS program.The results of the study revealed that early childhood teachers in Hafr Al-Batin have a high degree of emotional intelligence, as it came in the first place after empathy with an arithmetic mean (2.65). In the second degree came the dimension of motivation with an arithmetic mean (2.63), and in the fifth and last degree came the dimension of self-control with an arithmetic mean (2.50). In light of the of the study findings, the researcher recommended the need to work to increase interest in emotional intelligence among early childhood teachers in the Hafr Al-Batin region in the Kingdom of Saudi Arabia.
Keywords: Emotional intelligence; level of performance; early childhood